DOLANAN MABARONG-BARONGAN PERFORMING ARTS OF BADUNG REGENCY AT THE BALI ARTS FESTIVAL XXXII (2010) - Ayu Srinatih, I Gusti (E-Journal of Cultural Studies; Volume 7, Number 2, May 2014)
Dolanan is a childrens game which is done while singing in order to have fun. As one of the cultural heritage, dolanan contains great national values which can be imparted into children as the foundation of character building thus having a platform and a strong identity. Nowadays dolanan is marginalized because children are more fond with various types of imported games which is packaged with sophisticated technology that makes them increasingly kept away from its own cultural roots. This reality is really concerning because we can lose an effective tool in imparting cultural values which is important for character building. Based on that reality, a research is conducted entitled “Dolanan Mabarong- barongan Performing Arts of Badung Regency at the Bali Arts Festival XXXII in 2010”. The problem that is the focus of this research is the factors that led to the creation of representation of Dolanan Mabarong-barongan of Badung Regency in the XXXII Bali Arts Festival in 2010. This research is a qualitative research, viewed from cultural studies prespective. To dissect the problem, the social practices theory of Pierre Bourdieu is used. The result of this research is that the factors that led to the creation of the representation of dolanan mabarong-barongan are the Bali Arts Festival, the ideology of the artist, the creativity of artists, community, arts education institutions, government policies, and globalization.
Keywords: performing arts, dolanan mabarong-barongan, Bali Arts Festival.